2003ネン ニ オケル ナンキョク ドームフジ キチ ナイ ノ オンド ト シツド - 亀田, 貴雄; カメダ, タカオ; 谷口, 健治; タニグチ, ケンジ; 高橋, 暁; タカハシ, キョウ; 栗崎, 高士; クリサキ, タカシ; Kameda, Takao; Taniguchi, Kenji; Takahashi, Kyo; Kurisaki, Takashi (2008)
P(論文) 南極ドームふじ基地内の生活環境を明らかにすることを目的として,2003年2月11日から2004年1月14日まで基地の建物内部の7カ所の室内温度を熱電対で10分ごとに測定した(欠測期間: 7月19日～8月17日).この期間中,アスマン型通風乾湿計により建物内部の6カ所で相対湿度を3回測定した.この結果,平均温度は,発電棟24.7℃,食堂23.5℃,観測棟21.1℃,居住棟内個室18.2℃,廊下18.2℃,食料庫8.2℃,旧掘削場-51.3℃ であることがわかった.この期間中の平均気温(屋外の雪面から1.5m高で測定)は-54.4℃ であった.2003年10月31日から11月10日にかけてブロッキング高気圧の発達に伴い,ドームふじでは気温が最大約30℃ 上昇したが,建物内部でも5-8℃ 程度温度が上昇した.この時は建物屋上の積雪の一部が融解し,融解水が建物の中に浸透した.このような融雪は,越冬中この期間のみ起こった.一方,建物内部の相対湿度は加湿器を室内で使用した時には25% 前後,加湿器を使用しない時は9.0% から22.9% であった. In order to clarify the living condition in Dome Fuji Station in 2003, air temperature and relative humidity in the station were measured. Thermocouples with data logger and a ventilated psychrometer were used for the measurements. Average air temperature from February 11, 2003 to January 14, 2004 (missing period: July 19 to August 17) in the Dome Fuji Station buildings were as follows: Generator room 24.7℃, Dining room 23.5℃, Observation room 21.1℃, Dormitory room 18.2℃, Corridor 18.2℃, Food storage 8.2℃ and Old ice coring site -51.3℃. Average outside air temperature (1.5m height from the snow surface) during the period was -54.4℃. A remarkable increase of outside air temperature (+30℃ at maximum) due to a blocking high event was observed from October 31, 2003 to November 10, 2003 at Dome Fuji, during which increase of air temperature from 5 to 8°C in the station buildings was recorded. Snow on the station buildings was partly melted and some of the melted water penetrated into the station. This was the only time snow melted during the wintering over party's stay at the station. Average relative humidity in the station buildings obtained using a small humidifier was about 25%; the relative humidity without using the humidifier ranged from 9.0 to 22.9%. departmental bulletin paper